Hydrogen peroxide in neutrophil inflammation: Lesson from the zebrafish. (April 2020) - Martínez-Navarro, Francisco J.; Martínez-Morcillo, Francisco J.; de Oliveira, Sofia; Candel, Sergio; Cabas, Isabel; García-Ayala, Alfonsa; Martínez-Menchón, Teresa; Corbalán-Vélez, Raúl; Mesa-del-Castillo, Pablo; Cayuela, María L.; Pérez-Oliva, Ana B.; García-Moreno, Diana; et al.
Abstract: The zebrafish has become an excellent model for the study of inflammation and immunity. Its unique advantages for in vivo imaging and gene and drug screening have allowed the visualization of dual oxidase 1 (Duox1)-derived hydrogen peroxide (H2 O2 ) tissue gradients and its crosstalk with neutrophil infiltration to inflamed tissue. Thus, it has been shown that H2 O2 directly recruits neutrophils via the Src-family tyrosine kinase Lyn and indirectly by the activation of several signaling pathways involved in inflammation, such as nuclear factor κB (NF-κB), mitogen activated kinases and the transcription factor AP1. In addition, this model has also unmasked the unexpected ability of H2 O2 to induce the expression of the gene encoding the key neutrophil chemoattractant CXC chemokine ligand 8 by facilitating the accessibility of transcription factors to its promoter through histone covalent modifications. Finally, zebrafish models of psoriasis have shown that a H2 O2 /NF-κB/Duox1 positive feedback inflammatory loop operates in this chronic inflammatory disorder and that pharmacological inhibition of Duox1, but not of downstream mediators, inhibits inflammation and restores epithelial homeostasis. Therefore, these results have pointed out DUOX1 and H2 O2 as therapeutic targets for the treatment of skin inflammatory disorders, such as psoriasis. Highlights: The zebrafish model has allowed visualization of Duox1-derived H2 O2 tissue gradients. H2 O2 mediates neutrophil infiltration to inflamed tissue through Lyn-mediated direct recruitment. H2 O2 mediates neutrophil infiltration indirectly by the activation of several signaling pathways. H2 O2 to induce cxcl8 expression via histone covalent modifications. A H2 O2 /NF-κB/Duox1 positive feedback inflammatory loop operates in psoriasis.